Cardiac Computed Tomography and Magnetic Resonance Imaging in the Evaluation of Mitral and Tricuspid Valve Disease: Implications for Transcatheter Interventions. (March 2017) - Naoum, Christopher; Blanke, Philipp; Cavalcante, João L.; Leipsic, Jonathon
Abstract : Transcatheter interventions to treat mitral and tricuspid valve disease are becoming increasingly available because of the growing number of elderly patients with significant comorbidities or high operative risk. Thorough clinical and imaging evaluation in these patients is essential. The latter involves both characterization of the mechanism and severity of valvular disease as well as determining the hemodynamic consequences and extent of ventricular remodeling, which is an important predictor of future outcomes. Moreover, an assessment of the suitability and risk of complications associated with device-specific therapies is also an important component of the preprocedural evaluation in this cohort. Although echocardiography including 2-dimensional and 3-dimensional methods has an important role in the initial assessment and procedural guidance, cross-sectional imaging, including both computed tomographic imagning and cardiac magnetic resonance imaging, is increasingly being integrated into the evaluation of mitral and tricuspid valve disease. In this review, we discuss the role of cross-sectional imaging in mitral and tricuspid valve disease, primarily valvular regurgitation assessment, with an emphasis on the preprocedural evaluation and implications for transcatheter interventions. Abstract : Supplemental Digital Content is available in the text.